PENGARUH MEDIA POP UP BOOK DALAM MENGENALKAN KOSAKATA ANGKA BAHASA INGGRIS PADA ANAK DI TK NEGERI 02 PANCUNG SOAL - Sari, Novita; Muryanti, Elise; Pransiska, Rismareni; Saridewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the underdeveloped ability of children to recognize English number vocabulary, which was caused by the limited use of engaging and varied learning media. As a result, children experienced difficulties in recognizing, pronouncing, and remembering English number vocabulary. Therefore, this study focused on the use of Pop-Up Book media as a learning medium that could attract children's attention and facilitate their understanding of English number vocabulary. This study employed a quantitative approach using a quasi-experimental research design. The population consisted of all children at TK Negeri 02 Pancung Soal. The sample was selected using a cluster sampling technique, involving Class B1 and Class B3, with 10 children in each class. Data were collected through a test consisting of four assessment items. The data were analyzed using normality testing, homogeneity testing, and hypothesis testing with the assistance of SPSS Version 25.The results indicated that the data from both the experimental and control groups were normally distributed and homogeneous. The hypothesis testing showed a significance value (Sig. 2-tailed) of 0.004. Since 0.004 was less than 0.05 (0.004 < 0.05), the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Therefore, it can be concluded that the use of Pop-Up Book media had a significant effect on children's ability to recognize English number vocabulary at TK Negeri 02 Pancung Soal. The findings also revealed that Pop-Up Book media effectively improved children's ability to recognize, pronounce, and understand English number vocabulary compared with conventional learning that did not use Pop-Up Book media.